2020
DOI: 10.1111/bcp.14422
|View full text |Cite
|
Sign up to set email alerts
|

First‐in‐human study of the safety, tolerability, pharmacokinetics and pharmacodynamics of single and multiple oral doses of SAR247799, a selective G‐protein‐biased sphingosine‐1 phosphate receptor‐1 agonist for endothelial protection

Abstract: SAR247799 is a selective G-protein-biased sphingosine-1 phosphate receptor-1 (S1P 1) agonist with potential to restore endothelial function in vascular pathologies. SAR247799, a first-in-class molecule differentiated from previous S1P 1-desensitizing molecules developed for multiple sclerosis, can activate S1P 1 without desensitization and consequent lymphopenia. The aim was to characterize SAR247799 for its safety, tolerability, pharmacokinetics and pharmacodynamics (activation and desensitization). Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
13
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 33 publications
(74 reference statements)
4
13
2
Order By: Relevance
“…Furthermore, these preclinical findings showed translation to human studies, where SAR247799 showed improvement in endothelial function in type-2 diabetes patients, again at sub-lymphocyte-reducing doses [12]. SAR247799 displayed an attractive safety and tolerability profile in humans, and supratherapeutic doses were characterized by dose-dependent lymphocyte reduction, a biphasic effect consistent with that observed in preclinical studies [11,12,13].…”
supporting
confidence: 63%
“…Furthermore, these preclinical findings showed translation to human studies, where SAR247799 showed improvement in endothelial function in type-2 diabetes patients, again at sub-lymphocyte-reducing doses [12]. SAR247799 displayed an attractive safety and tolerability profile in humans, and supratherapeutic doses were characterized by dose-dependent lymphocyte reduction, a biphasic effect consistent with that observed in preclinical studies [11,12,13].…”
supporting
confidence: 63%
“…Indeed, we showed in the present study in Ob-ZSF1 rats, that SAR247799, through its mechanism of action on endothelial function, reduced VLF bands of systolic blood pressure variability, an index of endothelial nitric oxide pathway activation (23). Similarly, our previous work shows that SAR247799 improves coronary microvascular reserve in a pig model of ischemic injury (15) and endothelial and renal function in diabetic rats (16). Furthermore, SAR247799 improves flow-mediated dilation in type-2 diabetes patients (16).…”
Section: Discussionsupporting
confidence: 79%
“…Effects of SAR247799 on physiological parameters SAR247799 was incorporated in the chow at the dose of 250 mg/kg as a previous study from our laboratory demonstrated the effect of this dose in endothelial protection in another rat model of metabolic dysfunction (16). In this study, the plasma concentration of SAR247799 after 4 weeks of treatment was 7-fold higher in young compared to the old ZSF1 rats.…”
Section: 8mentioning
confidence: 64%
“…However, in none of the treatment groups was blood pressure or BAD (prehyperaemia) altered compared to placebo; findings consistent with an absence of blood pressure effect with SAR247799 in healthy subjects. 52 Although S1P modulates blood pressure by acting on vascular smooth muscle (S1P 2/3 ) and endothelium (S1P 1/3 ), a lack of functional S1P 1 receptors on vascular smooth muscle, [81][82][83] lends further support that our FMD results with SAR247799 are unlikely to be influenced by a direct action on vascular smooth muscle.…”
Section: Concurrent Therapy Nmentioning
confidence: 56%
“…50,51 In healthy subjects, SAR247799 has an attractive safety, tolerability and pharmacokinetics (PK) profile and the dose-response relationship for lymphocyte pharmacodynamics (PD) has been characterized. 52 Although preclinical studies with SAR247799 showed protective effects in the renal and coronary vasculature in a preventative setting using single doses administered prior to an insult of ischaemia/reperfusion-induced endothelial injury, the effect of chronic administration of SAR247799 on the endothelium is currently unknown. Furthermore, as previous molecules were S1P 1− desensitizing, the effect of S1P 1 activation on endothelial properties in patients has not yet been studied.…”
Section: What This Study Addsmentioning
confidence: 99%